Analysis of Youth’s Low Interest in Congregational Prayer and Its Implications for Community Implementation - Mukaddam, Muhammad Faqih; Huda, Nuril (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
Prayer is the most important worship that will be accounted for on the Day of Judgment. Prayer performed in congregation has a higher value than prayer performed alone, which is one degree to twenty-seven degrees. In this regard, the researcher wants to conduct a study related to the factors of low interest of young people in congregational prayer and its implications for community congregational prayer. The importance of this study is that the researcher really hopes that the mosque or langgar will be prosperous by establishing congregational prayer, especially by its young people. The approach used in this study is a qualitative approach. This study uses observation, interview and questionnaire data collection techniques. The researcher observed and used unstructured interviews with the community and distributed questionnaires to young people in Sungai Kali Village, Batang Kulur Kiri Village and Batang Kulur Kanan Village. The results of this study are that it can be seen about the factors of low interest of young people in carrying out congregational prayer, namely the lazy factor, the far from the mosque factor, the busy/work/school factor, the no friends factor, the not used to it factor. The solution based on these problems, the researcher provides a solution for the committee to create a community that attracts the attention of young people to go to the mosque/langgar. These communities include sports communities, discussion communities and so on.